Efektivitas aplikasi parenting mobile terintegrasi budaya lokal ngada “nalo” terhadap literasi anak usia dini - Wea, Ludgardis; Fono, Yasinta Maria; Meka, Marsianus; Nafsia, Andi (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2026)
Early childhood literacy skills at TKK Generasi Unggul are still low due to the lack of varied and interactive learning media. The purpose of this study is to determine the effectiveness of the mobile-based parenting application "Nalo," which is integrated with the local Ngada culture, on children's literacy skills. This quantitative research used a Pre-Experimental design (One Group Pretest-Posttest) involving 17 children aged 5-6 years. The instrument used was literacy skills observation, which has been validated. Data were analyzed using a paired sample t-test. The study results showed a significant increase in average literacy scores from 10.82 (pretest) to 14.71 (posttest). Statistical test results showed t(16) = −8.056  with p < 0.001, and a very large effect size. The conclusion is that the "Nalo" application is effective in improving children's literacy through aspects of letter recognition, arranging letters, and reading words